ANALISIS STRATEGI PEMASARAN LANTING MENGGUNAKAN METODE SWOT DAN QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) DI UMKM LANTING AGUNG: ANALYSIS OF LANTING MARKETING STRATEGIES USING SWOT AND QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) METHODS IN LANTING AGUNG - elsa indrianto (Journal of Optimization System and Ergonomy Implementation, 2025)
Competition between UMKM who produce similar products will become increasingly competitive, requiring business actors to always maintain and pay full attention to the quality of the products produced. This research aims to achieve the expected goals. With a management strategy, business activities will be more focused and adapt to increasingly complex business developments. The results of the QSPM analysis show that the strategy of maximizing location which is a strategy to attract potential market share has the highest TAS score of 3,62; the strategy of improving and maintaining product quality to maintain customer connections has a TAS score of 3,38; as well as the strategy of providing discounts and better service. good for maintaining customer loyalty has a TAS score of 2,80. The recommended strategy that should be implemented by the company is to maximize strategic locations to attract potential market share.